MODELLING OF THE ENERGY NEEDED FOR DEFROSTING OF WOOD MATERIALS IN THE HYGROSCOPIC RANGE (Innovation in Woodworking Industry and Engineering design, 2026)
A mathematical model of the specific heat energy, which is needed for defrosting of wood materials in the hygroscopic range, dfr q , has been suggested. The specific heat energy d fr q consist of two parts: the energy needed for heating of the frozen wood until melting of the ice in it, wfr q , and the energy needed for the melting of the ice formed from the bound water in the wood, bwq . Using the suggested model computations have been carried out for the determination of wfr q , bwq , and d fr q = wfr q + bwq during defrosting of oak, pine, beech, and poplar frozen wood with moisture content from 0.2 kg·kg-1 up to the border of the hygroscopic diapason and with initial temperature in the range from −20 oC to −2 oC, at which the thawing of the ice formed from the bounded water is completed.